Reaching the full potential of cryo-EM reconstructions with molecular dynamics simulations at 310 K: Actin filaments as an example - Sahithya Sridharan Iyer; Kristina M. Herman; Tamsuk Paul; Yihang Wang; Thomas D. Pollard; Gregory A. Voth (Proceedings of the National Academy of Sciences, 2025)
Cryoelectron microscopy (cryo-EM) structures of multiprotein complexes such as actin filaments help explain the mechanisms of assembly and interactions with partner proteins. Yet, rapid cooling during freezing may not preserve the conformations at physiological temperature. All-atom molecular dynamics simulations starting with cryo-EM reconstructions can provide additional insights. For example, at 310 K, adenosinediphosphate (ADP)-actin filaments fluctuate on a nanosecond time scale around higher entropy states with partly twisted subunits and smaller rotations along short-pitch helix than the cryo-EM reconstructions, while cryogenic temperatures favor flattened conformations. In the active site, the positions of Q137 and the catalytic water 1 and activating water 2 optimal for in-line attack on the γ-phosphate of ATP are very rare at 310 K, explaining in part the slow rate of ATP hydrolysis in filaments. This favorable arrangement of the waters is not observed in simulations of actin monomers. At 310 K, subunits in ADP-P i -actin filaments have their backdoor gates open 60% of the time for phosphate release, a conformation not observed by cryo-EM. Rare fluctuations open binding sites for cofilin and phalloidin. The twisted conformations of pointed end subunits and interactions of the D-loop of the penultimate subunit explain the slow association of new subunits. The terminal subunit at the barbed end is tethered to its neighbor along the long-pitch helix but dissociates transiently from its lateral neighbor. These effects of subfreezing temperatures on actin filaments are surely not an isolated example, so molecular dynamics simulations of structures of other frozen proteins will be informative.